2016
DOI: 10.1016/j.virol.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Jumonji C-domain containing protein 6 (JMJD6) in infectivity of foot-and-mouth disease virus

Abstract: Foot-and-mouth disease virus (FMDV) utilizes four integrins (αvβ1, αvβ3, αvβ6, and αvβ8) as its primary cell receptor. During cell culture propagation, FMDV frequently adapts to use heparan sulfate (HS), and rarely utilizes an unidentified third receptor. Capsid mutations acquired by a soluble integrin resistant FMDV cause (i) adaptation to CHO-677 cells (ii) increased affinity to membrane-bound Jumonji C-domain containing protein 6 (JMJD6) (iii) induced JMJD6 re-localization from the cell surface and cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 66 publications
3
26
0
Order By: Relevance
“…Residue 95 is located at the interface between two VP1 proteins at the fivefold axis of the virus particle and interacts with the C-terminus of the Jumonji C-domain containing protein 6 (JMJD6) [52,64]. A substitution of glutamic acid with lysine at this position allows the virus to infect cells in culture in an integrin-and HS-independent manner [30,52,64].…”
Section: Virus Protein Vp1mentioning
confidence: 99%
“…Residue 95 is located at the interface between two VP1 proteins at the fivefold axis of the virus particle and interacts with the C-terminus of the Jumonji C-domain containing protein 6 (JMJD6) [52,64]. A substitution of glutamic acid with lysine at this position allows the virus to infect cells in culture in an integrin-and HS-independent manner [30,52,64].…”
Section: Virus Protein Vp1mentioning
confidence: 99%
“…This assumption is supported through studies using an A 24 Cruzeiro mutant (A-SIR #42) that harbors the same E95K change in VP1 [ 17 ]. Further studies revealed this amino acid change to be responsible for utilizing Jumonji C-domain containing protein 6 to infect cells in an integrin- and HS-independent way [ 43 ]. Indeed, in the present study, A 24 -2P was the only mutant capable of infecting CHO677 cells, which do neither have surface integrins nor HS.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the viral particles isolated from vesicular fluid and tissue samples of these animals confirmed no alterations in the capsid sequence, showing that the JMJD6-FMDV mutant virus was indeed causing the clinical disease. The authors also postulate that differences in the degree of virulence based on the route of inoculation could be due to the non-accessibility of the key components of the third receptor pathway by aerosol route of inoculation [66,67]. …”
Section: Jmjd6 and Virusesmentioning
confidence: 99%